Partner support and interactions with communities show mixed effects on governance of community‐based resources - Eleanor Roxburgh; Morena Mills; Sangeeta Mangubhai; Alifereti Tawake; Margaret Vakalalabure; Hugh Govan; Arundhati Jagadish; Tanya O'Garra (Conservation Science and Practice)
Abstract Community‐based natural resource management is recognized as an effective area‐based conservation approach. Accordingly, conservation organizations worldwide are providing support to local communities seeking to sustainably manage and use their local natural resources. However, there is little understanding of how different types of support provided by partner organizations influence local community governance of these resources. Our data, collected from Fiji using key informant interviews, demonstrates that there is no clear association between partner support and effective community governance of marine resources. While no associations were evident when investigating the effects of partner support on participation and perceived fairness of decision‐making at the village level, some significance was identified when investigating responses by social group. We did find a clearer signal, however, with regards to the types of interaction between partners and communities, such that regional meetings were associated with increased community knowledge of the boundaries of the customary fishing grounds and village meetings were associated with increased ecosystem monitoring. Our work underscores the need to evaluate how different types of support from partner organizations, and the manner in which they interact with communities, impact community‐based conservation initiatives.